Synthesis of the first water-soluble C-2-symmetric bis(oxazolidinone) as a potential bifunctional chiral auxiliary - Lee, SG; Lim, CW; Kim, DC; Lee, JK (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
The first water-soluble C-2-symmetric bis(oxazolidinone) 1, a potential bifunctional chiral auxiliary, has been synthesized via regioselective intramolecular cyclization of a biscarbamate. The sodium enolate derived from N,N'-di(phenylacetyl)bis(oxazolidinone) 7 reacts with methyl iodide with high facial selectivity (95:5). (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: ASYMMETRIC ALDOL REACTIONS; ALKYLATION REACTIONS; EVANS OXAZOLIDINONE; 1,3-DIACYLIMIDAZOLIDIN-2-ONES; HYDROSILYLATION; 1,2-DIAMINES; DERIVATIVES; ALDEHYDES; ALCOHOLS; LIGANDS